In-vitro antioxidative potential of methanolic aerial extracts from three ethnomedicinal plants of Assam: A Comparative Study - Kabita Mahato, Bibhuti Bhusan Kakoti, Sudarshana Borah, Mritunjay Kumar (Journal of Applied Pharmaceutical Science, 2015)
Antioxidants are the substances that neutralize free radicals or their actions. The traditional antioxidant phytochemicals from plants have been reported to inhibit the propagation of free radical reactions and to protect the human body from disease. The use of synthetic antioxidants has always been questioned because of their toxicity therefore researches are being carried out on plants nowadays to bring out the potent natural antioxidants. With this intent three ethnomedicinal plants of Assam viz., Calamus leptospadix Griff., Heliotropium indicum Linn., Lasia spinosa Lour. were explored with a view to evaluate their in-vitro antioxidative potentials. The methanolic aerial extracts were studied for phytochemical analysis and antioxidative properties by different in-vitro assays: DPPH radical scavenging method, Nitric oxide radical scavenging activity, Hydrogen peroxide radical scavenging activity, Total phenolic content and Total flavonoid content. The percentage of inhibition was calculated by comparing the absorbance values of the control and test samples. The study conducted revealed that methanolic extract of Calamus leptospadix (CL) exhibited the highest DPPH radical scavenging activity (IC50 value of 29 ± 3.24 μg/ml), Nitric oxide radical scavenging activity (233.33 ± 3.54 μg/ml), Total phenolic content (8.02 ± 0.32 μg/ml expressed as gallic acid equivalents) and Total flavonoid contents (61.71 ± 1.16 μg/ml expressed as quercetin equivalents). Methanolic extract of Lasia spinosa (LS) showed highest hydrogen peroxide radical scavenging activity (IC50 value of 221.89 ± 2.14 μg/ml). The results obtained in the present study indicate that aerial parts of Calamus leptospadix have potent, Lasia spinosa have moderate and Heliotropium indicum (HI) have mild antioxidant and free radical scavenging activity.
Keywords: Calamus leptospadix Griff., Lasia spinosa Lour., Heliotropium indicum Linn., Antioxidative potential, DPPH.